PRINSIP-PRINSIP BAHASA RUPA - Tabrani, Primadi (Jurnal Budaya Nusantara, 2018)
The concept of Fine Language is the result of the creation of a long research, originally in the form of a researchreport on the science of Fine Language which later developed into dissertation research as much and as thick as 'onecoffin' (58x33x37cm). This Fine Language is a way of 'reading' pictures, from various images, pictures of children,prehistoric cave pictures, wayang beber pictures, then to symbolic images, decorative images and shadow images fromshadow puppets (wayang kulit). Also included are temple relief images and modern drawings, animated images, filmsand pictures produced by other digital technologies, such as ad images. The word language is different from the imagelanguage. In the image language, we can already describe the shape of the drawn. In the word language, use the word torepresent an object that is drawn. Often experience miscommunication because with various words (from different regions/tribes/countries) to describe an object. In the language of the image there are wimbas, in the wimba there is thecontent of wimba and way of wimba. The content of the wimba is a picture contained in the wimba, and the way thewimba is how the wimba is drawn and can be told. Through the 'science' is the original image that is beginning to beunderstood and retold as teaching materials or materials of scientific art for future studies, about the image of traditionsand modern drawings.